Implementasi Safety Culture Petugas Aviation security (AVSEC) PT Angkasa Pura 1 terhadap Keamanan dan Keselamatan Bandar Udara Adi Soemarmo Boyolali Jawa Tengah - Kusumawardana, Andika Rimba; Prayudhista, Eka (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Air transportation has a very important role as a means of connecting quickly and effectively. In the city of Boyolali there is the Adi Soemarmo international airport which has a fairly busy flight activity. The main factor that must be considered in the aviation industry is creating aviation security and safety which has been regulated in Government Regulation No. 3 of 2001. For the sake of creating this, efforts must be made, one of which is by implementing a safety culture. One unit that has an important role is Aviation Security (AVSEC) officers at Adi Soemarmo Boyolali Airport. In this study the authors used qualitative research methods using primary data and secondary data. For data collection techniques, namely by conducting interviews with Aviation Security (AVSEC) officers, observing directly (observation) during the official hours of Aviation Security (AVSEC) officers and carrying out documentation. The results of this study indicate that Aviation Security (AVSEC) personnel in carrying out their roles and responsibilities have implemented a Safety Culture which consists of six characters namely commitment, truth, information, alertness, adaptation and attitude in accordance with Standard Operational Procedures set by the company. Thus, Aviation Security personnel are able to create flight security and safety in accordance with Government Regulation No. 3 of 2001. Keywords: Aviation Security (AVSEC), Safety Culture.